1999
DOI: 10.1200/jco.1999.17.9.2859
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Trial of Interferon Alfa-2a Plus Vinblastine Versus Vinblastine Alone in Patients With Advanced Renal Cell Cancer

Abstract: The combination of IFNalpha2a plus VLB is superior to VLB alone in the treatment of patients with locally advanced or metastatic renal cell carcinoma. This is the first study to demonstrate that survival can be prolonged by using IFNalpha2a for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
179
1
17

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 404 publications
(206 citation statements)
references
References 32 publications
9
179
1
17
Order By: Relevance
“…This finding is in accordance with the results of two recent randomised phase III trials in mRCC demonstrating a significant but only modest effect of IFN-a (Medical Research Council Renal Cancer Collaborators, 1999;Pyrhonen et al, 1999). Thus, a British study with a total of 335 patients randomised to subcutaneous IFN-a or oral medroxyprogesterone acetate (MPA) (Medical Research Council Renal Cancer Collaborators, 1999) demonstrated a significant absolute improvement in 1-year survival of 12% (43 vs 31%) and a significant improvement in median survival of 2.5 months (8.5 vs 6.0 months) for IFN-a-treated patients compared to MPA-treated patients.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is in accordance with the results of two recent randomised phase III trials in mRCC demonstrating a significant but only modest effect of IFN-a (Medical Research Council Renal Cancer Collaborators, 1999;Pyrhonen et al, 1999). Thus, a British study with a total of 335 patients randomised to subcutaneous IFN-a or oral medroxyprogesterone acetate (MPA) (Medical Research Council Renal Cancer Collaborators, 1999) demonstrated a significant absolute improvement in 1-year survival of 12% (43 vs 31%) and a significant improvement in median survival of 2.5 months (8.5 vs 6.0 months) for IFN-a-treated patients compared to MPA-treated patients.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have been published in the past 10 years looking at the efficacy of interferon (MRCRC Collaborators, 1999;Pyrhonen et al, 1999), IL-2 (Yang et al, 2003b;McDermott et al, 2005;Tannir et al, 2006), and antivascular-targeted therapies (Hainsworth et al, 2005;Escudier et al, 2007;Motzer et al, 2007) in the treatment of patients with metastatic RCC. These treatments demonstrate incremental gains in survival (MRCRC Collaborators, 1999;Pyrhonen et al, 1999), a small but consistent and durable complete response rate (Yang et al, 2003b;McDermott et al, 2005) or prolonged progression-free survival rates (Hainsworth et al, 2005;Escudier et al, 2007;Motzer et al, 2007).…”
Section: Vaccination Of Metastatic Rcc Patients E Jonasch Et Almentioning
confidence: 99%
“…These treatments demonstrate incremental gains in survival (MRCRC Collaborators, 1999;Pyrhonen et al, 1999), a small but consistent and durable complete response rate (Yang et al, 2003b;McDermott et al, 2005) or prolonged progression-free survival rates (Hainsworth et al, 2005;Escudier et al, 2007;Motzer et al, 2007). From a clinical perspective, vitespen does not reach the threshold of therapy when compared to these other agents.…”
Section: Vaccination Of Metastatic Rcc Patients E Jonasch Et Almentioning
confidence: 99%
See 2 more Smart Citations